Prevalence of Acute Q Fever Among High-Risk Patients With Fever and Pneumonia Symptoms in Western Iran - Amjad Ahmadi; Rasool Nasiri Kalmarzi; Behzad Mohsenpour; Parisa Esmaeili; Mina Latifian; Ahmad Ghasemi; Rashid Ramazanzadeh; Himen Salimizand; Daem Roshani; Saber Esameili; Ehsan Mostafavi (Journal of Tropical Medicine)
Conclusion: The results of this study showed that there are cases of acute Q fever in Western Iran, but it is not considered by the healthcare system or clinicians.